Smoothed empirical likelihood confidence intervals for the relative distribution with left-truncated and right-censored data - Molanes-lopez, Elisa M.; Cao, Ricardo; Keilegom, Ingrid VAN (Canadian journal of statistics, 2010)
The study of differences among groups is an interesting statistical topic in many applied fields. It is very common in this context to have data that are subject to mechanisms of loss of information, such as censoring and truncation. In the setting of a two-sample problem with data subject to left truncation and right censoring, we develop an empirical likelihood method to do inference for the relative distribution. We obtain a nonparametric generalization of Wilks' theorem and construct nonparametric pointwise confidence intervals for the relative distribution. Finally, we analyse the coverage probability and length of these confidence intervals through a simulation study and illustrate their use with a real data set on gastric cancer. L'étude de différences entre des groupes est un sujet d'étude statistique intéressant dans de nombreux domaines appliqués. Dans de tels contextes, il est fréquent d'avoir des données qui sont sujettes à un mécanisme de perte d'information tel que la censure ou la troncature. Dans le cadre d'un problème à deux échantillons avec données sujettes à la troncature à gauche et la censure à droite, nous développons une méthode de vraisemblance empirique pour faire de l'inférence sur la fonction de répartition relative. Nous obtenons une généralisation non paramétrique du théorème de Wilks et nous construisons des intervalles de confiance non paramétriques ponctuels pour la fonction de répartition relative. Finalement, nous analysons la probabilité de couverture et la longueur de ces intervalles de confiance à l'aide d'une étude de simulation. Leur utilisation est illustrée à l'aide de données sur le cancer de l'estomac.